2016
DOI: 10.1111/srt.12345
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of morphological changes after facial massage by a novel approach using three‐dimensional computed tomography

Abstract: Background/purpose: Photograph-based visual scoring has been used for evaluation of facial morphological changes. Here, we describe a three-dimensional computed tomography (3D-CT) method for objective analysis of facial and intra-facial (subcutaneous) changes. The effects of facial massage were examined using both methods. Methods: Subjects were 12 healthy female volunteers without facial scars or deformation (age 30-54 years, mean 39.4 years). Photograph-based scoring of massage-induced morphological changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In addition, we determined that SMAS laxity was greater in older subjects and that changes in their facial appearance were easily induced by a PC (Figure ). Our previous studies, in which the SMAS laxity was quantified using MDCT, revealed the usefulness of the imaging modality . Nonetheless, our current results provide objective evidence of the relationship between age and SMAS laxity, which is a significant cause of cheek sagging.…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…In addition, we determined that SMAS laxity was greater in older subjects and that changes in their facial appearance were easily induced by a PC (Figure ). Our previous studies, in which the SMAS laxity was quantified using MDCT, revealed the usefulness of the imaging modality . Nonetheless, our current results provide objective evidence of the relationship between age and SMAS laxity, which is a significant cause of cheek sagging.…”
Section: Discussionmentioning
confidence: 53%
“…To this end, the MDCT imaging modality was used to accurately measure the morphological changes in the SMAS that were associated with a posture change. Current CT imaging technology can provide high‐resolution images, allowing detailed visualization of the facial appearance and the subcutaneous anatomic structures . Moreover, the workstation, which serves as the image analysis device, can create various 3‐D CT images as well as reconstructed images.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…FSC of Japanese woman has also been reported to influence autonomic nerve system (ANS) activity [ 3 – 7 ]. Alternatively, facial massage by hand is thought to provide physical stimulation to both skin and muscle, leading to morphological and physical improvement [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%